Insecticide application did not reveal any impact of herbivory on plant roots in boreal forests - Kozlov Mikhail V; Zverev Vitali (ELSEVIER, 2022)
The levels of belowground herbivory in natural ecosystems remain practically undetermined, and nothing is known regarding the geographic and/or climatic variations in belowground herbivory. We endeavoured to narrow this knowledge gap by exploring the latitudinal changes in the intensity of background root herbivory in boreal forest ecosystems by conducting a herbivore exclusion experiment in 10 forested sites from 60N to 69N in northwestern Russia. We found no statistically significant differences in fine root biomass between diazinontreated and control plots, nor did the differences show any latitudinal change. From biomass of root-feeding macrofauna we estimated that root herbivory in our sites averages 0.57 %. This low level of root herbivory could not be quantified reliably by herbivore exclusion experiments; therefore, we suggest that macroecological patterns in root herbivory are invoked from simultaneous measurements of the biomasses of fine roots and of root-feeders. More data on the efficiency of conversion of the food ingested by root-feeding invertebrates is needed to increase the accuracy of the suggested method of estimation of root herbivory.